2021
DOI: 10.1021/acsabm.0c01472
|View full text |Cite
|
Sign up to set email alerts
|

3D Cell Culture: Recent Development in Materials with Tunable Stiffness

Abstract: It is widely accepted that three-dimensional cell culture systems simulate physiological conditions better than traditional 2D systems. Although extracellular matrix components strongly modulate cell behavior, several studies underlined the importance of mechanosensing in the control of different cell functions such as growth, proliferation, differentiation, and migration. Human tissues are characterized by different degrees of stiffness, and various pathologies (e.g., tumor or fibrosis) cause changes in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 175 publications
0
41
0
1
Order By: Relevance
“…5,6 Since the goal of the study is to create a system that mimics the tumor microenvironment, the 3D hydrogel model has been loaded with both tumor cells (A549) and fibroblasts (MRC-5) at different ratios (1:1 and 1:2). Taking into account that matrix stiffness strongly impacts on cell behavior, 7 two different GelMA formulations (Medium and High) have been used, characterized by different degrees of substitution. Then, to test the proliferation, MTT assay was performed at various time points.…”
Section: Resultsmentioning
confidence: 99%
“…5,6 Since the goal of the study is to create a system that mimics the tumor microenvironment, the 3D hydrogel model has been loaded with both tumor cells (A549) and fibroblasts (MRC-5) at different ratios (1:1 and 1:2). Taking into account that matrix stiffness strongly impacts on cell behavior, 7 two different GelMA formulations (Medium and High) have been used, characterized by different degrees of substitution. Then, to test the proliferation, MTT assay was performed at various time points.…”
Section: Resultsmentioning
confidence: 99%
“…This concept can be theoretically applied as a treatment whereby engineered materials may be implanted into tumor resection cavities after surgical removal of visible tumor. The material or scaffold could be engineered to respond to chemical and physical stimuli from surrounding brain tissue and to alter local physical properties to promote an anti-glioma microenvironment (114,116,(146)(147)(148)(149). This paradigm requires further study and is yet to be developed for clinical application in glioma.…”
Section: Theranostic Opportunities and Modeling Therapeutic Targetsmentioning
confidence: 99%
“…These models will be crucial for effective drug development because they may offer useful information about pharmacokinetic and pharmacodynamic properties of proposed therapeutics as well as uncover additional therapeutic targets or treatment resistance mechanisms. As new variables are identified that can influence the mechanical properties of the microenvironment, the models that attempt to recapitulate these features will likely continue to become more sophisticated (114,116,(147)(148)(149)(165)(166)(167).…”
Section: Preclinical Modelingmentioning
confidence: 99%
“…), influence bulk mechanical properties such as stiffness and porosity. Homogenous tuning of scaffold stiffness is a means to promote desired phenotypes [ 35 ]; soft (∼1 kPa) hydrogel substrates promote neurogenesis, whereas differentiation of glial cells is favoured on materials with an elastic modulus ∼1–10 kPa [ 22 , 27 ]. Modulation of scaffold stiffness is also suggested as a means to manipulate the secretome of encapsulated cells, further supporting the concept of mechanical control of cell fates [ 83 ].…”
Section: Biomaterialsmentioning
confidence: 99%
“…The concept of mechanical control of cell behaviour becomes increasingly relevant when we observe abnormal mechanical features (i.e. increased stiffness) in neurodevelopmental disorders, neurodegenerative disease and CNS injury [ 28 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%